Implementation of Problem-Based Learning Model with Ethnomathematics Nuance Towards Students’ Problem-Solving Ability and Mathematics Anxiety - Patmara, Reza; Wahyudin, Agus; Susilaningsih, Endang (Journal of Primary Education)
The purpose of this study was to analyze the effectiveness and influence of the problem-based learning model with ethnomathematics nuance towards problem-solving ability and mathematics anxiety. The type of research used is a mixed method with concurrent embedded research design. The technique of collecting data uses a problem-solving ability test, questionnaires, interviews, and documentation. Data analysis technique using quantitative and qualitative analysis techniques. Quantitative data analysis techniques include proportion test, average difference test, direct effect test, moderating variable test, and Triangulation of qualitative data. The subject of research amounted to 78 students. The results showed that (1) The problem-based learning model with mathematical nuances effectively increased the average problem-solving ability to reach 75% classical completeness with zvalue = 1.64 > ztable = 1.64, (2) The average score of problem-solving in experiment class was 74.6 and control class was 68.9 with tvalue = 2.56 > ttable = 1.99, (3) There was a positive direct effect of model problem-based learning with ethnomathematics nuance on problem-solving ability with tvalue = 84.11 at the level of 0.00, (4) Mathematics anxiety can strengthen the influence of problem-based learning with ethnomathematics nuance on problem-solving ability was 0.002 at sig level of 0.02, (5) Student with low anxiety can complete all of problem-solving stages, students wih moderate anxiety can understand the problem develop a plan, but less able to carry out the plan, and students with high anxiety can understand problems, but less able to develop a plan and implement a plan.